2020
DOI: 10.1111/1750-3841.15080
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously fermented curly kale juice: Microbiological quality, nutritional composition, antioxidant, and antimicrobial properties

Abstract: Nondairy fermented products, such as fruit and vegetable juices, are gaining popularity among consumers worldwide for health-related and economic reasons. The purpose of this study was to determine the changes in microbiological quality; antimicrobial and antioxidant activity; and phenolic, vitamin C, minerals, and cadmium content occurring during spontaneous fermentation of curly kale juice. The fermentation process contributed to a significant growth of lactic acid bacteria, enterococci, and yeasts, while no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 44 publications
2
7
0
2
Order By: Relevance
“…In the subsequent stages of fermentation and storage, a decrease in the Leuconostoc population corresponded with the succession of Lactobacillus species, notably L. plantarum, L. coryniformis, and L. sakei. As was shown in our previous research, a drop in pH value from 5.08 on day 2 to 4.08 on the last day of fermentation was observed (Szutowska et al 2020). Therefore, it can be concluded that, bacteria of the genus Lactobacillus acted as strong acid producers.…”
Section: Isolation and Identification Of Lactic Acid Bacteria By Maldsupporting
confidence: 74%
See 2 more Smart Citations
“…In the subsequent stages of fermentation and storage, a decrease in the Leuconostoc population corresponded with the succession of Lactobacillus species, notably L. plantarum, L. coryniformis, and L. sakei. As was shown in our previous research, a drop in pH value from 5.08 on day 2 to 4.08 on the last day of fermentation was observed (Szutowska et al 2020). Therefore, it can be concluded that, bacteria of the genus Lactobacillus acted as strong acid producers.…”
Section: Isolation and Identification Of Lactic Acid Bacteria By Maldsupporting
confidence: 74%
“…As shown in our previous studies on fermented curly kale juice (Szutowska et al 2020), after 48 h of spontaneous fermentation, obligate aerobic microorganisms and fungi decreased, while the number of LAB, enterococci, and yeasts increased significantly. Thus, the initial microbiota activity resulted in the creation of an optimal environment for other microorganisms, responsible for stronger acidification of the product and the successful completion of the fermentation process (Szutowska et al 2020). In the subsequent stages of fermentation and storage, a decrease in the Leuconostoc population corresponded with the succession of Lactobacillus species, notably L. plantarum, L. coryniformis, and L. sakei.…”
Section: Isolation and Identification Of Lactic Acid Bacteria By Maldsupporting
confidence: 70%
See 1 more Smart Citation
“…En fermentaciones espontáneas hay menor control sobre los microorganismos que pueden crecer, un ejemplo de ello es el jugo de zanahoria, que tiene mayor cantidad de BAL en comparación con las enterobacterias, 8 de 20 cepas identificadas por secuenciación pertenecen a Leuconostoc y Lactobacillus 110 ; igualmente en la fermentación espontánea de jugo de col rizada se encuentra mayor conteo de BAL y un nulo crecimiento de E. coli y Salmonella spp., la actividad antimicrobiana mejora durante la fermentación contra diferentes cepas patógenas (E. coli, S. enteritidis, Y. enterocolitica, P. aeruginosa, entre otras) 4 .…”
Section: Actividad Antimicrobiana De Jugos Fermentados Con Balunclassified
“…Este proceso de fermentación ha sido utilizado en este tipo de alimentos para mejorar su conservación, y determinar los cambios sobre las propiedades nutricionales de la actividad metabólica y enzimática de los microorganismos sobre el producto fermentado 3 . De los procesos fermentativos, el más estudiado es el del ácido láctico producido por las BAL, éstas son las más utilizadas en la fermentación de jugos y hortalizas debido a su inocuidad y beneficios a la salud humana 4 .…”
Section: Introductionunclassified